The formation of history as a discipline during early Islamic history - Akhmetova, Elmira (2019)
This paper highlights the importance of history as a discipline and a branch of knowledge in early Islamic intellectual life. It first underlines that Islam, as a creed and culture, is a history-conscious religion that was born among the Arabs, who inherited well-established methodologies of oral tradition and writing of genealogies from their history-loving ancestors, thus facilitating the formation of history as a branch of revealed knowledge (naqli) along with ‘ilm al-hadith and ‘ilm al-tafasir as early as the second century after the hijrah.